Dynamical observations on the crack tip zone and stress corrosion of two-dimensional MoS2 - Thuc Hue Ly (Nature Portfolio, 2017)
How well the linear elastic fracture picture holds at small length scales and systems with reduced dimensionality remains an active area of inquiry. Here authors usein situ electron microscopy to study fracture in MoS2monolayers and report dislocation emission rates greater than expected accompanying crack propagation.